Social Change and Legal Compliance Among Tattoo Removal Participants in the Brave Wani Hijrah Kudus Community - Riyadi, Fuad (ADDIN, 2024)
The Tattoo Removal program serves as a driving force for spiritual transformation and significant social change, helping individuals and communities enhance their religious and social lives. As part of the hijrah process, this initiative plays a crucial role in promoting social transformation and strengthening legal awareness. This study explores the Tattoo Removal program by Brave Wani Hijrah and Rehab Hati Kudus, examining the factors that motivate participants to join and analyzing the resulting social changes and legal awareness among them. A qualitative approach is employed, utilizing case study methods, in-depth interviews, and participant observation. The findings indicate that the Tattoo Removal program effectively fosters positive change in participants, including tangible social transformation, heightened legal awareness, increased self-confidence, greater community acceptance, and a stronger commitment to legal compliance. These results highlight the significance of programs like Tattoo Removal as tools for social transformation and legal consciousness.